An X-FEM based framework for 3D fatigue crack growth using a B-spline crack geometry description. (15th February 2022) - Hectors, Kris; De Waele, Wim
Abstract: This paper presents an X-FEM based iterative framework for numerical simulation of three-dimensional fatigue crack propagation. To accurately describe the crack geometry, B-spline curves and surfaces are used for the crack front and faces respectively. A new crack front extension method based on the Möller–Trumbore algorithm is introduced to achieve fully automated crack growth for complex geometries. To validate the presented work, three different cases are discussed: (1) compact tension specimens with an asymmetrically located hole, (2) a beam with a slanted crack subjected to a three-point bending load and (3) a beam with a slanted crack subjected to a torsion load. Good agreement between the numerical and experimental results is observed. Highlights: A Python based iterative framework for three-dimensional fatigue crack propagation. B-spline formulation based crack surface and crack face description. A new, robust, crack front extension method for simulation of 3D crack growth in complex geometries. Good agreement between numerical and experimental results.